Comparison of different virtual chromoendoscopy classification systems for the characterization of colorectal lesions. Issue 5 (7th July 2020) - Zorron Cheng Tao Pu, Leonardo; Yamamura, Takeshi; Nakamura, Masanao; Koay, Doreen S C; Ovenden, Amanda; Edwards, Suzanne; Burt, Alastair D; Hirooka, Yoshiki; Fujishiro, Mitsuhiro; Singh, Rajvinder
Abstract: Background and Aim: Commonly used classifications for colorectal lesions (CLs) include the Narrow Band Imaging (NBI) International Colorectal Endoscopic (NICE) and Japan NBI Expert Team (JNET) classifications. However, both lack a sessile serrated adenoma/polyp (SSA/P) category. This has been addressed by the modified Sano's (MS) and Workgroup serrAted polypS and Polyposis (WASP) classifications. This study aims to compare the accuracy of wNICE and wJNET (WASP added to both) with the stand‐alone MS classification. Methods: Patients undergoing colonoscopy at an Australian tertiary hospital who had at least one CL detected were prospectively enrolled. In the exploratory phase, CLs were characterized in real time with NBI and magnification using all classifications. In the validation phase, CLs were assessed with both NBI and Blue Laser Imaging (BLI) by four external endoscopists in Japan. The primary outcome was the comparison of wJNET and MS. Secondary outcomes included comparisons among all classifications and the calculation of interrater reliability. Results: A total of 483 CLs were evaluated in real time in the exploratory phase, and four sets of 30 CL images (80 on NBI and 40 on BLI) were scored in the validation phase. For high‐confidence diagnoses, MS accuracy was superior to wJNET in both the exploratory (86% vs 79%, P < 0.05) and validation (85% vs 69%, P < 0.05) phases. The interrater reliability was substantial for all classifications ( κ = 0.74, 0.69, and 0.63 for wNICE, wJNET, and MS, respectively). Conclusions: MS classification achieved the highest accuracy in both the exploratory and validation phases. MS can differentiate serrated and adenomatous polyps as a stand‐alone classification. Abstract : Many classifications have been propose to characterize colorectal lesions but few include SSA/Ps.Comparison between classifications that have this potential lack in the literature.This study compares the WASP+NICE, WASP+JNET and MS classifications with NBI and BLI imaging.